2019
DOI: 10.1002/jcp.28323
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA‐145 in protection against myocardial ischemia/reperfusion injury in mice by regulating expression of GZMK with the treatment of sevoflurane

Abstract: This study aims to investigate the role of microRNA‐145 (miR‐145) in protection against myocardial ischemia/reperfusion (I/R) injury in mice by regulating expression of granzyme K (GZMK) with the treatment of sevoflurane. The mice model of myocardial I/R injury was established by left coronary artery ligation. The expression of miR‐145 and GZMK in myocardial tissues of mice was detected by Reverse transcription quantitative polymerase chain reaction and western blot analysis. The changes of the cardiac functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…For example, a previous study reported that miR-145-5p promoted the apoptosis of cardiomyocytes after myocardial I/R in rats (12). However, other studies demonstrated that miR-145-5p protected against myocardial I/R injury in murine models via anti-apoptotic, anti-inflammatory and autophagy pathways (10,11,29). Hence, the role of miR-145-5p in myocardial I/R injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a previous study reported that miR-145-5p promoted the apoptosis of cardiomyocytes after myocardial I/R in rats (12). However, other studies demonstrated that miR-145-5p protected against myocardial I/R injury in murine models via anti-apoptotic, anti-inflammatory and autophagy pathways (10,11,29). Hence, the role of miR-145-5p in myocardial I/R injury remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…miR-145 is highly expressed in the vasculature and its role in the cardiovascular system has been extensively investigated (7)(8)(9). A few studies have explored the role of miR-145-5p in myocardial I/R (10)(11)(12). However, the results of these studies were inconsistent and the role of miR-145-5p in myocardial I/R remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…As GrK is a potential target gene of miRNA-145, miRNA-145 could inhibit GrK expression. Upon treatment with sevoflurane, miRNA-145 levels are upregulated and GrK expression is reduced – relieving I/R injury ( 90 ). Interestingly, miRNA-145 significantly elevates functioning of the left ventricle and decreases the myocardial infarct size suggesting that downregulation of GrK and upregulation of miRNA-145 may be protective of I/R injury ( 90 ).…”
Section: Grk As a Therapeutic Targetmentioning
confidence: 99%
“…Furthermore, Yuan et al [10] proved that miR-145 exerted a cardioprotective effect in myocardial I/R injury by ameliorating inflammation via regulation of CD40 in vitro. Moreover, prior studies [9, 11] have demonstrated that antagonizing miR-145 pretreatment significantly aggravated myocardial I/R injury by deteriorating infarcted myocardium size, apoptosis, and inflammation in mouse. Although miR-145 may represent a novel potential therapeutic target, its role in cardiac I/R injury in vivo is still unclear.…”
Section: Introductionmentioning
confidence: 99%